Enhancing Students’ English Skills through English Workshop Implementation at SMA Bhaktyarasa Maumere - Etu, Maria Florida (Universitas Nurul Jadid, 2025)
This research investigates the implementation of an English workshop and its impact on enhancing students’ English skills at Bhaktyarsa Senior High School. The study is driven by the concern that many high school students in Indonesia demonstrate low English proficiency due to limited focus on language development in the curriculum. The objective of this study is to provide educators with insights into creating more effective and engaging English learning environments. Employing a qualitative descriptive method, the research collected data through observation, interviews, focus group discussions, and document analysis. The findings reveal that the English workshop was effectively implemented through structured stages, including Warm-up Activities, Topic Presentation, Guided Discovery Learning, Practice and Application, and Feedback and Reflection. These activities led to noticeable improvements in students’ speaking fluency and vocabulary mastery. Furthermore, students responded positively to the workshop, showing increased motivation, confidence, and enthusiasm in using English both academically and in daily communication. The results highlight the potential of interactive workshops in addressing the challenges of English language acquisition at the high school level in Indonesia, offering practical implications for educators seeking to enhance language instruction